The Lived Experiences of NCAA Athletes with One or Multiple Concussions - Jocelyn Schwegler; Kristin Mauldin; Kerri Racin-Anderson; Alexandra Hotetz; Jaimee Stutz-Johnson; Laiyatu Manya; Kamonie Davis; Melanie Estrada (Trauma Care)
Background/Objectives: Concussions, their physical presentation, and patients’ recovery have been researched and documented numerous times, but the experiences of surviving and recovering from a concussion need to be explored further. The purpose of this study was to examine the lived experiences of NCAA Division I, II, and III student athletes who had suffered from one or more concussions. Methods: The consensual qualitative research (CQR) methodology was employed, guiding the formation of the interview questions and the analysis of the responses. The participants completed a free-response questionnaire as well as a semi-structured virtual interview that utilized a blend of idiographic, inductive, hermeneutic, and interpretive phenomenological approaches. Through their questionnaire and interview responses, they discussed their experience being concussed at a collegiate level. Results: Ten NCAA student athletes described their various physical, cognitive, emotional, and sleep-related symptoms due to receiving their concussion(s). Many of these student athletes reported feelings of loneliness, being misunderstood, or even not feeling “normal or at baseline” during and after their concussion recovery. One primary finding was the key role the athletic trainers played in the student athletes’ recovery process from initially receiving the concussion to their return to play. Conclusions: These findings will help contribute to the knowledge of what it is like to experience one or multiple concussions, the recovery process, and how that process can be improved.